Yam tuber and maize grain yield response to cropping system intensification in south-west Nigeria - Enesi, R.O.; Hauser, S.; López Montez, A.; Osonubi, O. (Informa UK Limited, 2018)
Four factorial trials were conducted with yam (Dioscorea rotundata Poir.) at Ibadan, Nigeria from 2013 to 2015, investigating effects of (1) tillage (2) fertilizer (3) intercropping (4) yam plant densities. Yam tuber yields varied between years (2013: 16.44 Mg ha−1; 2014: 10.08 Mg ha−1; 2015 26.61 Mg ha−1). In 2013 neither tillage nor fertilizer affected tuber yields. In 2014 tillage increased yields (+25.4%, P < 0.0001), fertilizer reduced yield (−10.5%; P = 0.0046). In 2015 tillage increased tuber yields by 8.1% (ns), fertilizer application increased yield (+17.5%, P = 0.0017). Across the years, tuber yields increased (P < 0.01) with increasing yam density with a constant increase in 2013 up to the highest density, yet yields leveled out above 14,815 plants ha−1 in 2014 and 2015. Intercropping with maize (66,667 plants ha−1) reduced tuber yield by 42.62% in 2013, 44.52% in 2014 and 30.68% in 2015 (P < 0.01 all years) across all yam densities. Maize grain yield was higher in sole crop in 2 years. Fertilizer increased yields in all years (P < 0.0001). Maize yield had no response to the yam densities. Ridging had a negative effect on grain yield in 2015 (−0.3 Mg ha−1, P = 0.0002). Increasing plant density appears a safe measure to increase yam yields.